Conductive silver paste and preparation method thereof
By using the combination of silver powder, auxiliary conductive powder, oxide and alloy powder in conductive silver paste, combined with the combination of epoxy resin and coupling agent, the conductivity, scratch resistance and solvent resistance in the prior art are solved. The problem of insufficient results enables high conductivity, wear resistance and low cost conductive silver paste, which is suitable for a variety of applications.
Patent Information
- Application Number
- CN202210254842.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-03-15
AI Technical Summary
The existing conductive silver paste has shortcomings in taking into account both conductivity, scratch resistance, hardness and solvent resistance, and it is difficult to achieve excellent performance and low cost requirements at the same time.
Conductive silver paste composed of silver powder, auxiliary conductive powder, oxide, alloy powder, resin and coupling agent, is formed by processing in specific proportions and processes, including the slurry with excellent conductivity, wear resistance and adhesion, including Nano-nickel powder, nano-silver-covered copper powder, oxide, alloy powder and epoxy resin were prepared using a three-roller machine.
The high conductivity, wear resistance and adhesion of conductive silver paste is achieved. The number of wipes on the coated film layer reaches 3697 times, and the square resistance performance reaches 28.6mΩ/□, which is suitable for a wide range of applications.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive ink, and in particular to a conductive silver paste and a preparation method thereof. Background Art
[0002] With the advent of the 5G era, the requirements for mobile phone signals are getting higher and higher. At present, the back cover of mobile phones is usually made of glass to enhance the mobile phone signal. In order to make the back cover of the mobile phone have a gorgeous appearance, a decorative film is usually attached to the inside of the glass shell, and conductive silver paste is printed on the decorative film. Conductive silver paste has a significant effect on enhancing the mobile phone signal.
[0003] Conductive silver paste is a special functional material, generally composed of a conductive functional phase, a matrix resin bonding phase, a solvent and other auxiliary additives. The conductive functional phase is mostly conductive metal powder, while the matrix resin bonding phase is mostly glass powder and high molecular polymer. Its main function is to provide adhesion and mechanical support for the paste. The conductive silver paste is printed on the paste carrier by a certain printing method, and solidified under a certain temperature and time. The conductive silver paste can be firmly attached to the carrier. The cured conductive silver paste has excellent conductivity, hardness, adhesion and bending resistance.
[0004] Patent CN201510319292.X provides a conductive silver paste and a preparation method thereof, the method comprising silver powder preparation and conductive silver paste preparation; the conductive silver paste preparation is carried out according to the following steps: a resin and a solvent are mixed in a mass ratio of 1:5 to 1:10, heated to 35 to 80°C, stirred for 3 to 8 hours, and heating is stopped after the resin is completely dissolved to obtain a dissolved resin; wherein the resin is at least one of bisphenol A epoxy resin, saturated copolymer resin, polyurethane, and hydroxy acrylic resin, and the solvent is at least one of isophorone, ethylene glycol butyl ether acetate, and diethylene glycol butyl ether; the prepared silver powder is dispersed in a solvent to obtain a silver powder dispersion, wherein the mass ratio of the silver powder to the solvent in the silver powder dispersion is 1:3 to 1:10, the silver powder dispersion is added to the dissolved resin, the mass ratio of the dissolved resin to the silver powder dispersion is 5:1 to 9:1, the two are stirred evenly, and dispersed with a three-roll mill to obtain the conductive silver paste. Although the conductive silver paste in the prior art has good conductivity, it cannot take into account the characteristics of good conductivity, scratch resistance, hardness and solvent resistance. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a conductive silver paste based on silver powder, which has the characteristics of excellent conductivity, scratch resistance, hardness, solvent resistance, low cost and the like.
[0006] On the one hand, the present invention provides a conductive silver paste comprising silver powder, auxiliary conductive powder, oxide, alloy powder, resin, and coupling agent.
[0007] Furthermore, in terms of mass percentage, the silver powder accounts for 10-80% of the conductive silver paste, preferably 15%, 20%, 25%, 30%, 35%, 40%, 50%, 60%, 70%, 80% and the range between any two of the above points, for example, 15%-80%, 25-70%, etc.
[0008] Further, the auxiliary conductive powder includes at least one of nano nickel powder and nano silver coated copper powder. The auxiliary conductive powder is 5-40% of the mass of the conductive silver paste, preferably 5%, 6%, 8%, 10%, 13%, 16%, 20%, 25%, 30%, 40%, and the range between any two of the above points, such as 8%-40%, 10-25%, etc. Further, the auxiliary conductive powder includes nano nickel powder and nano silver coated copper powder, wherein the nano nickel powder is 5-30% and the nano silver coated copper powder is 0.01-20%. Preferably, the nano nickel powder is 5%, 8%, 10%, 13%, 16%, 20%, 25%, 30%, and the range between any two of the above points, such as 5-25%, etc. Preferably, the nano silver coated copper powder is 0.01%, 1%, 2%, 5%, 10%, 13%, 17%, 20%, and the range between any two of the above points, such as 1-10%, etc.
[0009] Further, the oxide includes at least one of silicon dioxide and zirconium oxide. The oxide dosage is 0.01-35%, preferably 0.1%, 1%, 5%, 10%, 13%, 16%, 20%, 25%, 30%, 35%, and the range between any two of the above-mentioned point values, such as 1%-30%, 10-25%, etc. Further, the oxide includes silicon dioxide and zirconium oxide. Among them, silicon dioxide 0.01-15%, zirconium oxide 0.01-20%. Preferably, silicon dioxide is 0.1%, 1%, 3%, 5%, 7%, 10%, 12%, 13%, 15%, and the range between any two of the above-mentioned point values, such as 1-13%, etc. Preferably, zirconium oxide is 0.01%, 1%, 2%, 5%, 10%, 13%, 17%, 20%, and the range between any two of the above-mentioned point values, such as 2-17%, etc.
[0010] Further, the alloy powder includes at least one of iron-chromium-nickel-copper-niobium alloy, nickel-chromium alloy, iron-nickel alloy, silver-clad iron-chromium-nickel-copper-niobium alloy, silver-clad nickel-chromium alloy, silver-clad iron-nickel alloy, and silver-clad nickel powder. The amount of the alloy powder is 0.01-30%, preferably 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 15%, 18%, 20%, 22%, 24%, 26%, 28%, 29%, 30%, and the range between any two of the above points, such as 3-13%.
[0011] Further, the resin is an epoxy resin, preferably one or both of bisphenol A epoxy resin and bisphenol F epoxy resin, preferably bisphenol A epoxy resin. The amount of epoxy resin is 0.01-15%, preferably 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, and the range between any two of the above points, such as 0.5-13%.
[0012] Further, the coupling agent is one or more of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, Dynasylan 1146 bisaminosilane coupling agent, 3-aminopropyltriethoxysilane, titanium coupling agent, and aluminum coupling agent. Preferably, the coupling agent is 3-(2,3-epoxypropoxy)propyltrimethoxysilane. Wherein, the amount of the coupling agent is 0.01-15%, preferably 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, and the range between any two of the above point values, such as 0.5-13%, etc.
[0013] Furthermore, the conductive silver paste of the present invention may also contain at least one of 0-10% silver-coated silicon carbide, 0-5% silver-coated silicon dioxide, 0-5% silver-coated cobalt oxide, and 0-5% silver-coated zirconium oxide.
[0014] Furthermore, the conductive silver paste of the present invention also contains a diluent. The diluent is one or more of 3,3'-(oxybismethylene)bis(3-ethyl)oxetane, ethyl 2-(oxetane-2-yl)acetate, 1,4-butanediol diglycidyl ether, phenyl glycidyl ether, p-tert-butylphenyl glycidyl ether, neopentyl glycol diglycidyl ether, isophorone, cyclohexanone, propylene glycol methyl ether acetate, acetylacetone, cyclohexyl acetate, and butyl acetate. Preferably, the diluent is one or a mixture of two of 1,4-butanediol diglycidyl ether and propylene glycol methyl ether acetate. The amount of the diluent is 0.01-15%, preferably 0.01%, 0.5%, 1%, 2%, 4%, 6%, 7%, 8%, 10%, 12%, 14%, 15%, and the range between any two of the above points, such as 2-15%.
[0015] Furthermore, the conductive silver paste of the present invention also contains a curing agent. The curing agent is one or more of a microcapsule imidazole curing agent, a microcapsule amine curing agent, and a microcapsule cationic curing agent. Preferably, one or more of the shell layers of the microcapsule imidazole curing agent, the microcapsule amine curing agent, and the microcapsule cationic curing agent are polyurethane resin materials. The curing agent may preferably be a microcapsule imidazole curing agent, and it is further preferred that the core layer of the microcapsule imidazole curing agent is an imidazole curing agent and / or the core layer is an imidazole curing agent. The amount of curing agent is 0.01-2%, preferably 0.01%, 0.05%, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2% and the range between any two of the above point values, such as 0.05-0.5%, etc.
[0016] Further, the conductive silver paste of the present invention also contains a toughening resin. The toughening resin is one or more of epoxidized polybutadiene resin, polyether polyol, polyurethane modified epoxy resin, core-shell epoxy resin, amino modified epoxy resin, reactive liquid nitrile rubber, and nano-enhanced material. The nano-enhanced material is one or more of functional methyl methacrylate-butyl acrylate-functional methyl methacrylate triblock copolymer, functional methyl methacrylate-butyl acrylate diblock copolymer, and styrene-butadiene-methyl methacrylate triblock copolymer. The toughening resin is one or two of amino modified epoxy resin and core-shell epoxy resin. The toughening resin is used in an amount of 0.01-8%, preferably 0.01%, 0.05%, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8% and the range between any two of the above-mentioned point values, such as 0.5-5%.
[0017] Furthermore, the silver powder, oxide, auxiliary conductive powder and alloy powder are all spherical or quasi-spherical, and are a mixture of particles of different particle sizes; wherein the average particle size of the silver powder, oxide and alloy powder is 0.001-10 μm, preferably 0.01-10 μm, 0.1-9.5 μm, 0.5-8 μm, 1-7 μm.
[0018] Furthermore, the particle size of the conductive silver paste is 1-100 μm, preferably 1.5-70 μm, 2-60 μm, 3-50 μm, 4-40 μm, 4.5-30 μm, 5-20 μm.
[0019] Further, the curing temperature of the conductive silver paste provided by the present invention is 55-190°C, and the curing time is 0.1-4h. It is further preferred that the curing temperature is 60°C, 65°C, 70°C, 75°C, 85°C, 95°C, 105°C, 115°C, 125°C, 135°C, 145°C, 155°C, 165°C, 175°C, 190°C and the range between any two of the above point values. The curing time is 0.2h, 0.4h, 0.6h, 0.8h, 1h, 1.5h, 2h, 3h, 4h and the range between any two of the above point values, for example, 0.2-3h, etc.
[0020] Furthermore, the conductive silver paste of the present invention comprises: 10-80% silver powder, 5-30% nano nickel powder, 0.01-20% nano silver-coated copper powder, 0.01-15% silicon dioxide, 0.01-20% zirconium oxide, 1-15% alloy powder, 0.01-15% resin, and 0.01-15% coupling agent.
[0021] Furthermore, the conductive silver paste of the present invention comprises: 30-80% silver powder, 5-30% nano nickel powder, 0.01-20% nano silver-coated copper powder, 0.01-15% silicon dioxide, 0.01-20% zirconium oxide, 1-15% alloy powder, 0.01-15% resin, and 0.01-1.5% coupling agent.
[0022] On the other hand, the present invention provides a method for preparing the conductive silver paste, comprising: dissolving a resin in a diluent to form a resin solution; adding the remaining components to the resin solution and stirring and mixing them evenly to obtain a slurry; and grinding the slurry using a three-roll mill to obtain a conductive silver paste.
[0023] Furthermore, the rotation speed of the stirring and mixing is 10-5000 rpm, preferably 50-500 rpm.
[0024] Furthermore, the stirring and mixing process is controlled at a temperature of 1-45°C, preferably 10-45°C, 20-45°C. Beneficial Effects
[0025] The conductive silver paste with silver as the base material in the embodiment of the present invention has a silver-gray appearance; the conductive silver paste has a moderate viscosity and is suitable for coating.
[0026] The coating obtained by coating the conductive silver paste of the present invention has good wear resistance test performance, which can reach 3697 times of wiping resistance. The silicon dioxide, zirconium oxide and alloy powder of the present invention have a synergistic effect in increasing the wear resistance test performance, and the composite use of the epoxy resin and the coupling agent of the present invention can significantly increase the wear resistance effect of the conductive silver paste.
[0027] The conductive silver paste of the present invention has good adhesion, and the adhesion is significantly reduced by omitting the epoxy resin and the coupling agent. The conductive silver paste of the present invention has good acetone wiping resistance, and the coating film can still remain intact after being wiped with acetone for many times.
[0028] The product of the invention has good square resistance performance, which can reach 28.6mΩ / □, and has excellent conductivity and is widely used. DETAILED DESCRIPTION
[0029] In order to better understand the present invention, the present invention is further described below by way of examples. The examples are only used to explain the present invention and will not constitute any limitation to the present invention.
[0030] The raw materials and reagents used in the embodiments of the present invention are as follows: silver powder: TFSP-01, Chengdu Tianfu Metal Powder Co., Ltd.; nano nickel powder: Ni-GB0201, Jiangsu Boqian New Materials Co., Ltd.; nano silver-coated copper powder: CuAg-S0500, Jiangsu Boqian New Materials Co., Ltd.; silicon dioxide: Q029, Suzhou Jinyi New Materials Technology Co., Ltd.; zirconium oxide: ZH-ZrO2-03, Hefei AVIC Nanotechnology Development Co., Ltd.; epoxy resin 1: JER828, Mitsubishi Chemical (Shanghai) Co., Ltd.
[0031] The amounts of raw materials used in the embodiments and comparative examples are shown in the following table, in percentage by mass:
[0032] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Silver powder 60 40 75 60 60 60 Nano Nickel Powder 5 9 5 5 5 5 Nano silver coated copper powder 6 7 1 6 6 6 Silicon dioxide 5 9 4 5 5 0 Zirconia 5 10 3 5 5 10 Nichrome 3 7 2 3 3 3 Epoxy resin 1 4 6 2 4 4 4 1,4-Butanediol diglycidyl ether 10 10 6 10 9 10 Coupling agent 1: 3-(2,3-epoxypropoxy)propyltrimethoxysilane 1.5 1.5 1.5 0 1.5 1.5 Coupling agent 2: 3-aminopropyltriethoxysilane 0 0 0 1.5 0 0 Toughened resin MX125 0 0 0 0 1 0 Curing agent HX 3722 0.5 0.5 0.5 0.5 0.5 0.5
[0033] Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Silver powder 60 60 60 60 60 Nano Nickel Powder 5 5 5 5 5 Nano silver coated copper powder 6 6 6 6 6 Silicon dioxide 10 5 5 13 5 Zirconia 0 5 5 0 8 Nichrome 3 3 3 0 0 Epoxy Resin A 4 0 5.5 4 4 1,4-Butanediol diglycidyl ether 10 10 10 10 10 Coupling agent 1: 3-(2,3-epoxypropoxy)propyltrimethoxysilane 1.5 5.5 0 1.5 1.5 Coupling agent 2: 3-aminopropyltriethoxysilane 0 0 0 0 0 Toughened resin MX125 0 0 0 0 0 Curing agent HX 3722 0.5 0.5 0.5 0.5 0.5
[0034] The preparation method of the conductive silver paste in the above embodiments and comparative examples is as follows:
[0035] Weigh each raw material according to the amount provided in the table, dissolve the resin in the diluent to form a resin solution; add the remaining other ingredients to the above resin solution, and then stir and mix evenly at a speed of 100 rpm and control the material temperature to 25°C to obtain a slurry; grind the above slurry using a three-roll mill and control the slurry particle size to 5-20μm to obtain a conductive silver paste.
[0036] Performance test of conductive silver paste
[0037] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Appearance Color silver gray silver gray silver gray silver gray silver gray silver gray silver gray silver gray silver gray silver gray silver gray Viscosity (25±1℃, Pa*S) 42.1 41.3 49.6 43.5 47.8 41.0 43.5 42.7 41.9 40.8 42.1
[0038] The conductive silver pastes of Examples 1-5 and Comparative Examples 1-6 of the present invention, which are based on silver, are all silver-gray in appearance. The conductive silver pastes of the Examples and Comparative Examples have moderate viscosities and are suitable for coating.
[0039] The conductive silver paste prepared in the above-mentioned embodiment and comparative example was printed on a PET film with a coating thickness of 30 μm, and then baked and cured at 65° C. for 4 hours to obtain a conductive film.
[0040] The wear resistance of the prepared conductive film was tested using the RCA paper tape (275 g) wear resistance test standard; the test results are as follows.
[0041] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Wear times 3567 3653 3410 3376 3697 2651 2549 2365 2278 2503 2579
[0042] Examples 1-5 of the present invention all have good wear resistance test performance; Example 5 adds a toughening agent on the basis of Example 1, which can improve the wear resistance of the conductive silver paste to a certain extent. Compared with Example 1, only epoxy resin and coupling agent are omitted in Comparative Examples 3-4 of the present invention, and the wear times of Comparative Examples 3 and 4 are significantly reduced because epoxy resin and coupling agent can increase the coating performance of the conductive silver paste and the substrate. When the above components are omitted, the coating performance of the conductive silver paste is reduced, which has a greater impact on the surface properties of the film-forming material. Compared with Example 1, Comparative Examples 1, 2, 5, and 6 of the present invention omit silicon dioxide, zirconium oxide, alloy powder and zirconium oxide, alloy powder, respectively, and the wear times of the obtained conductive silver paste are significantly reduced; it may be because silicon dioxide, zirconium oxide, and alloy powder have good hardness, which can increase the hardness of the conductive silver paste and thus increase the wear resistance; and when one or more of them are omitted, the composite performance of silicon dioxide, zirconium oxide, and alloy powder cannot be maximized, thereby reducing the wear resistance of the product. By comparing comparative examples 1-6 with the embodiment, it can be seen that the silicon dioxide, zirconium oxide and alloy powder of the present invention have a synergistic effect in increasing the wear resistance test performance, and the compound use of the epoxy resin and the coupling agent of the present invention can significantly increase the wear resistance effect of the conductive silver paste.
[0043] The film adhesion is tested using the hundred-grid knife method, with grades ranging from 0B to 5B. The larger the value, the better the adhesion.
[0044] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Adhesion 5B 5B 5B 5B 5B 5B 5B 3B 3B 5B 5B
[0045] Examples 1-5 of the present invention all have good adhesion; Comparative Examples 3 and 4 of the present invention in which the epoxy resin and the coupling agent are omitted have poor adhesion.
[0046] Wipe the film layer with a non-woven paper towel soaked in acetone solvent, observe the changes in the film layer, and evaluate the solvent resistance of the film layer. Use a 500g weight to press the paper towel when wiping, and do it back and forth 30 times. Among them, √ means that the surface is basically unchanged; ○ means that the film layer is damaged, but the bottom layer is not leaked; × means that the film layer is damaged and the bottom layer is leaked. The test results are shown in the following table.
[0047] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Solvent resistance √ √ √ √ √ ○ ○ × × ○ ○
[0048] It can be seen from the test results in the above table that Examples 1-5 of the present invention all have good acetone-resistant wiping effects, and the conductive silver paste coating of the present invention can still remain intact after being wiped with acetone for multiple times.
[0049] 4. Square resistance performance test: The square resistance performance test of each embodiment and comparative example is shown in the following table.
[0050] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Square resistance (mΩ / □) 33.2 43.7 28.6 34.0 34.7 34.3 37.2 36.8 38.6 37.9 36.1
[0051] From the test results in the above table, it can be seen that Examples 1-5 of the present invention all have very good square resistance performance, which can reach 28.6 mΩ / □. The products of the present invention have excellent electrical conductivity and are widely used.
[0052] In addition, it should be understood that after reading the contents of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A conductive silver paste, characterized in that: In terms of weight percentage, the components are as follows: 40-80% silver powder, 5-10% nano nickel powder, 10-20% nano silver-coated copper powder, 5-13% silicon dioxide, 3-10% zirconium oxide, 2-10% alloy powder, 2-8% resin, 1-6% coupling agent, 6-12% diluent and 0.5-2% curing agent; Wherein, the nano nickel powder and nano silver-coated copper powder are auxiliary conductive powders; The silicon dioxide and zirconium oxide are oxides; The alloy powder is a nickel-chromium alloy; The resin is bisphenol A epoxy resin; The coupling agent is 3-(2,3-epoxypropoxy)propyltrimethoxysilane; The diluent is 1,4-butanediol diglycidyl ether.